A Building Microgrid Architecture Based on MMC-SST and its Control Strategy - WANG Yahui; LI Yong; HAN Jiye; CAO Yijia (Kongzhi Yu Xinxi Jishu)
In traditional building microgrid architecture, conventional power transformer is used for connecting to power grid. However, this architecture is unable to adapt to the development of building micorgrid with increasing distributed power supplies and sensitivity loads. Therefore, a novel architecture of building mocrogrid was presented in this paper, which is based on modular multilevel converter-solid state transformer (MMC-SST). Comparing with conventional power transformer, MMC-SST is relatively small, highly controlled and has both DC and AC interfaces, so it is able to coordinate the power flow between building microgrid and distribution network, and improve the power quality of system. In this way, the proposed architecture is more suitable for the development requirements of building microgrid. Additionally, internal mode control (IMC) method was applied at the stage control of MMC-SST, and the simplicity, controllability and robustness of this method are better than the traditional PI control based on dq decoupling method. Simulation results verified the superiority of the proposed building microgrid architecture in power quality control, and also demonstrate the advancement of IMC strategy in response speed and anti-disturbance ability comparing with PI control.